Rwanda Economic Update, May 2013 : Maintaining Momentum with a Special Focus on Rwanda's Pathway Out of Poverty - World Bank (Washington, DC, 2014)
The Rwanda economic update reports and synthesizes recent economic developments and places them in a medium term and global context. It analyzes the implications of these developments and policies for the outlook of Rwanda's economy. In this way, these reports contribute to the implementation of the Bank's Africa strategy. The economic update reports cover in each edition a special feature on a selected topic. It is intended for a wide audience, including policy makers, business leaders and other market participants, and the community of analysts, engaged in Rwanda's economy. Rwanda's economy is estimated to have grown by a robust 8 percent in 2012, continuing a decade-long period of strong economic growth. The economic expansion was driven by buoyant private sector activity, particularly in the services sector, where growth exceeded expectations. This strong economic performance has allowed Rwanda to claim for the third year in a row, the title of the fastest growing economy in the East African Community. The domestic economy remained strong despite an estimated 20 percent reduction in Official Donor Assistance (ODA) in 2012, following the intensifying of the conflict in Eastern Congo. Providing jobs to the two million people who will enter the workforce in the decade to come will be crucial to sustaining Rwanda's achievements.